Poetry as a Multidimensional Medium for Language, Literacy, and Social Reflection in Elementary Education - Diplan Diplan (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the Study: Poetry offers not only aesthetic value but also potential as a learning tool that supports children’s language growth, literacy competence, and social awareness. However, poetry is still rarely positioned as a multidimensional pedagogical medium in elementary education. Therefore, this study aims to analyze how poetry functions as a medium for language development, literacy education, and social reflection in elementary classrooms. Methodology: This study used a qualitative descriptive design involving six purposively selected elementary schools. Data were obtained from five Indonesian language teachers, twelve students, classroom observations, and documentation of students’ poetry works. Data were analyzed using the Miles, Huberman, and Saldana model, through data condensation, display, and conclusion drawing, with validity ensured using source and methodological triangulation. Main Findings: The findings indicate that poetry improves linguistic competence, particularly vocabulary, diction, and figurative language understanding. Poetry also strengthens students’ literacy through close reading, interpretive discussion, and creative writing engagement. Furthermore, poetry becomes a reflective tool for students to express environmental issues, family dynamics, friendship, and cultural identity. Novelty/Originality of this Study: This study demonstrates that poetry is a multidimensional learning medium that simultaneously develops language skill, literacy depth, and socio-emotional awareness. The novelty lies in its integration of three learning outcomes within one instructional model. Implicationally, poetry-based learning can be adopted as an alternative strategy for teachers to create contextual, expressive, and character-oriented literacy practices in elementary schools.